The big book of dyslexia activities for kids and teens : 100+ creative, fun, multi-sensory and inclusive ideas for successful learning - Reid, Gavin, 1950-; Guise, Nick; Guise, Jennie (Jessica Kingsley Publishers, 2018)
Full of interesting and creative activities for children and young people aged 5-19 with dyslexia, this book is an essential guide for teachers and parents. Focusing on practical and accessible projects, the guide will cover key skills such as listening, memory, talking and writing.